A Study on Color Application and Perception in Urban Neighborhood Renewal Based on Simulation Comparison: Taking the Case of Kuangdaxuefu Street in Xuzhou, China - He Fang; He Yong; Sun Liang (Lodz University of Technology Press, 2023)
For the emotional needs of architectural color diversity in the renewal of urban micro-scale areas in China, this study intends to explore the trends in color perception which are influenced by changes in architectural color characteristics. In this study, the main color characteristics that influence the urban color renewal were determined through the preliminary basic investigation in China. The color psychological perception experiments were conducted by combining VR technology with questionnaire, so as to determine the correlation between architectural color characteristics and main color perceptions, as well as the correlation between different color perceptions.
Keywords: urban renewal; urban color; color perception; color characteristic; rewitalizacja miast; kolor miejski; percepcja koloru; charakterystyka koloru